Farelo de arroz desengordurado e diferentes métodos de incorporação de fitase em dietas de poedeiras comerciais - Ebling, Patrícia Diniz (2011)
The enzyme phytase improves the utilization of various nutrients in plant foods, which are partly unavailable to non-ruminant animals, especially phytic acid, but beyond this also starch, proteins, lipids and other minerals, which are complexed with phytic acid. The effectiveness of this enzyme has been widely proven. Nevertheless, several studies were not successful in its use in feed for monogastric animals. This is due to the characteristics of sensitivity and specificity of phytases instability. Given these facts, the objective with the study to evaluate the most effective way of incorporating phytase in diets for laying hens in relation to performance, quality of eggs (experiment 1) and utilization of protein (experiment 2). The research was conducted in the laboratory of poultry Polytechnic College (UFSM). The experimental performance and egg quality of laying hens used 120 Isa Brown strain, being conducted in three periods of 21 days. The digestibility trial had 72 birds and lasted five days. Both experiments assessed the following diets: basal diet (BD), diet with defatted rice bran (DRB) previously treated with phytase (DRBF) diet with phytase enzyme and DRB incorporated through the traditional method (TMF) and a diet without DRB phytase (DRB). The experiment was a completely randomized design with four treatments, five replicates for experiment 1 and three replicates for experiment 2 with six birds. The data collected were submitted to analysis of variance and the means that differ significantly, Tukey (5%). The treatment of DRBF was efficient, ie, treating only one ingredient of the diet with phytase allows you to incorporate a smaller amount of phytase, while maintaining performance and quality of eggs, which were statistically the same (P> 0.05) in treatments involving phytase, equivalent also to the basal diet, indicating that phytase supplied the reduction of phosphorus in the treatment TMF. The treatment of DRB with phytase enabled better utilization of protein.